Travailler sur des objets en faisant se confronter les points de vue. Regards croisés sur le langage fou : l’exemple des écrits bruts - Vincent Capt (Les Cahiers de l'École du Louvre)
Using a text written in an asylum now archived in the Collection de l’Art Brut in Lausanne as a starting point, this article, a discourse analysis, proposes to examine the impact of points of view on not only collecting but also the status and formal content of the objects of study. With, as a backdrop, this strong credo: for a form to be, it has to signify; and it owes relatively little to the perspective that seizes it. It is initially a question of examining the point of view of psychiatry, then that of art regarding the "same objet", that is, a letter by Samuel Daiber. These points of view are then related to the theme of madness, using the notional couple "mania/manner" as a starting point. The specific historicity of the works related to art brut (particularly the written texts that initially came from psychiatric institutions) is thus examined in detail: going from a symptomatology of madness to a poetics of madness, it activated a theory of language and enabled society as a whole to be interpreted.